Car Body Assembly Process in Assemblyng Section at Suzuki Indomobil Motor Plant Cikarang Company - Prakoso, Sanjaya; Ratna Dewi Anjani; Aa Santosa (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This practical work was carried out at PT Suzuki Indomobil Motor Plant Cikarang with a focus on the car body assembly process in the assembling section. The assembling process is an important stage in vehicle manufacturing, where components of various sizes (small, medium, and large parts) are systematically assembled to form a complete car structure. Assembly is carried out sequentially from one station to another using a conveyor system, and involves various techniques and standard operating procedures to ensure the quality of the final result. Through this activity, students can directly understand the working system of the automotive industry, assembly methods, and gain experience in a professional work environment.